Circulating Betatrophin Levels Are Associated with the Lipid Profile in Type 2 Diabetes - Ghasemi, Hassan (Chonnam Med J, 2015)
Betatrophin is a newly characterized circulating hormone that is produced in tissues such as adipose tissue and liver and stimulates pancreatic beta-cell proliferation. The purpose of the current study was to examine circulating betatrophin levels in Iranian patients with type 2 diabetes mellitus (T2DM) and in normal controls. Seventy-five subjects were enrolled in this case-control study in the following two groups: T2DM patients (n=40) and a group of age-, sex-, and BMI-matched normal control subjects (n=35). Circulating betatrophin concentrations as well as the blood lipid profile, body mass index (BMI), fasting blood sugar (FBS), glycated hemoglobin (HbA1c), and insulin resistance were determined. Circulating betatrophin levels were significantly higher in patients with T2DM than in the normal subjects (4.79±1.53 ng/mL vs. 2.79±1.11 ng/mL respectively; p=0.001). Serum triacylglycerol and total cholesterol were also significantly higher in patients with T2DM than in the control group. In the patients with T2DM, serum betatrophin was positively correlated with age, FBS, TG, total cholesterol, and HbA1c. The results of this initial study in Iran have shown that circulating betatrophin levels are significantly increased in Iranian patients with T2DM compared with a control group. Additionally, it is postulated that betatrophin as a novel hormone may be involved in the generation of an atherogenic lipid profile.